Promoting form I′ crystallization and melting-recrystallization by adding a β-nucleating agent into poly(butene-1)/isotactic polypropylene blends. Issue 17 (14th April 2023) - Xu, Min; Han, Yu; Li, Xiangyang; Ding, Jianjun; Zheng, Kang; Lin, Yongxing; Chen, Lin; Tian, Xingyou
Abstract : As the main factor restricting the production of poly(1-butene), the slow phase transition of poly(1-butene) from form II to form I has not been avoided effectively because of the lack of effective methods. Abstract : As the main factor restricting the production of poly(1-butene), the slow phase transition of poly(1-butene) from form II to form I has not been avoided effectively because of the lack of effective methods. Blending with other polyolefins to directly transit into the stable form I′ crystals could be a possible solution; however, such a method hardly inhibits the formation of form II completely. What is worse, the obtained form I′ crystal even has a lower thermostability than that of form II, which makes it hard to be an ideal solution. In this study, employing FTIR spectroscopy, XRD, SEM, and POM, we found that adding a moderate amount of WBG-II, a nucleating agent of iPP, into isotactic polypropylene/poly(1-butene) (iPP/PB-1) blends could greatly promote the formation of form I′. More importantly, the melted form I′ can rapidly recrystallize into form II on heating, improving thermostability. The lower the quenching temperature, the more significant the role of WBG-II. We conjectured that the effect of WBG-II could be related to iPP chains in the PB-rich domains because the promotion effect of WBG-II becomes significant only when the PB-1 content is greater than 20% but smaller than 80%, where PB-rich domains may exist. The addition of WBG-II enhanced the nucleating ability of iPP chains in the PB-rich domains and therefore increased its ability to promote form I′ nucleation. After increasing the temperature above the melting point of form I′, the iPP nuclei formed under the assistance of WBG-II, in turn, act as nucleation sites of form II, promoting form I′ transiting into form II after melting. This study provides a new idea to avoid the influence of slow form II to form I phase transition on the production of PB-1 and improve the thermostability of PB-1.